[Something fishy ; Clay play ; Daring DAR [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Tackles the accusation of violation of the Anti-Pollution law by Century Tuna Corporation which dumped its waste into the Taguig River down to a fishing town in Laguna de Bay ; the story of how the Alcazaren brothers turned their talents for making clay figures into business ; and the new public trust on the Department of Agrarian Reform under Miriam Defensor Santiago after the Garchitorena land scam.